Wuthering heights’ three Chinese translated versions’ reception in China: Translation, publication, and dissemination - Qingqing Zhang; Charity Lee; Huzaina Abdul Halim (UNIB Press, 2022)
This study aims to explore the reception of Wuthering Heights in China by conducting comparative study on its three Chinese-translated versions, which were published in three periods, to examine how these versions have been translated, published, and disseminated. This study applies historical and archival research methods, close reading methods and comparative methods. The researchers collected the data from the original text of Wuthering Heights and its three Chinese-translated versions, relevant monographs, academic papers and information about the three versions. The academic papers were collected from China National Knowledge Infrastructure, the most authoritative database in China for scientific publications. The information of the three versions was obtained from the Chinese online Chaoxing database, which is the most extensive database that provides information on books based on big data. First, the researchers explored the translation journey of Wuthering Heights in China and the information of its three representative versions that appeared at different times. Second, the researchers investigated the publication route of the three versions, concentrating on the information of the publishing houses, the formats of the three versions and the reprint edition. Third, the researchers analyzed the dissemination of the three versions in the Chinese literary field, focusing on the library collections, citations and academic circle comments. This paper concludes that the translation and circulation process of the three versions promoted the dissemination of Wuthering Heights in China to a great extent. The reasons for the extensive dissemination of Wuthering Heights in China are its excellent charm, translators and scholars’ efforts and Chinese readers’ passion for it.